2016
DOI: 10.4236/jbpc.2016.74009
|View full text |Cite
|
Sign up to set email alerts
|

MorphologicaObservation of Specific Condensation Effect of Cholesterol on Dipalmitoyl Phosphatidyl Choline (DPPC) Monolayer by Dropping Method

Abstract: Morphology of dipalmitoyl phosphatidyl choline (DPPC)-cholesterol (Chol) mixed monolayer formed on water surface by dropping method was investigated using surface tension measurement (STm), Brewster angle microscopy (BAM), and fluorescence microscopy (FM). STm showed strong condensation effect of Chol in fluidic DPPC monolayer. Excess area (S ex ) from mean mixing state of DPPC and Chol was about twice larger than that by general compression method in the range from x C = 0.2 to 0.4 (x C : mole fraction of Cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 17 publications
4
10
1
Order By: Relevance
“…A 0 was 0.39 ± 0.02 nm 2 /molecule at 30 mN/m of π and this value was also very similar (0.40 nm 2 /molecule at 35 mN/m) in compression method [22] [23] [24] [25]. The obtained A 0 was also identical (0.41 nm 2 /molecule at 34 mN/m) as reported previously by dropping method [11].…”
Section: Surface Tension Measurement (Stm)supporting
confidence: 86%
See 2 more Smart Citations
“…A 0 was 0.39 ± 0.02 nm 2 /molecule at 30 mN/m of π and this value was also very similar (0.40 nm 2 /molecule at 35 mN/m) in compression method [22] [23] [24] [25]. The obtained A 0 was also identical (0.41 nm 2 /molecule at 34 mN/m) as reported previously by dropping method [11].…”
Section: Surface Tension Measurement (Stm)supporting
confidence: 86%
“…Therefore the deviation occurred in both the methods suggests that the DMPC-cholesterol mixed monolayer formation by dropping and compression methods are same and thus cholesterol condensation effect of the mixed monolayer is also same in both methods. The result of cholesterol condensation effect on DMPC monolayer was different from that of dipalmitoyl phosphatidyl choline (DPPC) monolayer, where the condensation effect of cholesterol on DPPC monolayer by dropping method was twice larger than compression method [11]. was brightest among all the above three π values, thereby confirmed that the completion of monolayer occurred at the water surface.…”
Section: Surface Tension Measurement (Stm)mentioning
confidence: 87%
See 1 more Smart Citation
“…Brewster angle microscopy (BAM) for visualizing the morphology of pure DPPC and DMPC and several mixed monolayers were carried out using a commercial BAM microscope (EMM633K; Filgen Inc., Nagoya, Japan) attached with an USB-CAP type (GV-USB2; I-O DATA DEVICE, INC., Kanazawa, Japan) imaging analysis software [16], [17], [18], [19], [20]. BAM shows the monolayer image arises from the difference in refractive index between the monolayer and the water phase.…”
Section: Brewster Angle Microscopy (Bam)mentioning
confidence: 99%
“…However, the study of DPPC-DMPC lipid combination is a pending issue. Therefore, in this communication, we have investigated the monolayer properties of two-dimensional DPPC-DMPC mixed monolayer at various mole fractions formed by the dropping method [16], [17], [18], [19] using surface tension measurement (STm), Brewster angle microscopy (BAM), and infrared external reflection spectroscopy (IERS).…”
Section: Introductionmentioning
confidence: 99%